Novel Approach Towards the Synthesis of Poly Heterocyclic Compounds: Total Synthesis of 12-Oxa-6,10b-epoxy-4b,5,6,10b,11,12-hexahydrochrysene - Kaur, Jasamrit (Asian Journal of Chemistry, 2017)
A simple and facile synthesis of the hexahydrochrysene derivative, 12-oxa-6,10b-epoxy-4b,5,6,10b,11,12-hexahydrochrysene has been reported through the use of conventional and green methodologies. The key steps are, microwave assisted O-alkylation of a bromophenol ether, synthesis of halosynthon, 1,4-dihydro-1,4-epoxynaphthalenyl methyl o-bromophenyl ether via reaction with benzyne formed in situ followed by its subsequent 6-exo-trig cyclization towards the synthesis of the polycyclic ring system in good yield.